2017
DOI: 10.1002/nau.23206
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire survey to assess lower urinary tract symptoms in patients with chronic stroke

Abstract: Storage symptom is associated with not only neurological deficits but also sex and the presence of general diseases, whereas voiding symptom is influenced by physical activity in patients with chronic stroke. Therefore, lower urinary tract symptoms should be carefully monitored and physical rehabilitation should also be considered in patients with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…Several questionnaires have been developed to evaluate the lower urinary tract symptoms. 11,12,17,18 Of these, the CLSS questionnaire addresses 10 important lower urinary tract symptoms, selected from the 25 symptoms defined by the International Continence Society, as having the greatest impact on QoL, in both men and women. 11 Using the CLSS, we confirmed the absence of any significant lower urinary tract symptoms in our study group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several questionnaires have been developed to evaluate the lower urinary tract symptoms. 11,12,17,18 Of these, the CLSS questionnaire addresses 10 important lower urinary tract symptoms, selected from the 25 symptoms defined by the International Continence Society, as having the greatest impact on QoL, in both men and women. 11 Using the CLSS, we confirmed the absence of any significant lower urinary tract symptoms in our study group.…”
Section: Discussionmentioning
confidence: 99%
“…The study group included 18 participants, 16 women, and 2 men with an average age of 40.8 years (Table ), average body mass index of 23.4, and no history of voiding symptoms, as confirmed using the Core Lower Urinary Tract Symptom Score (CLSS) questionnaire. The CLSS evaluates 10 important lower urinary tract symptoms known to have the greatest negative impact on the QoL of symptomatic men and women: daytime frequency, nocturia, urgency, urgency incontinence, stress incontinence, slow stream, straining, incomplete emptying, bladder pain, and urethral pain. Each item is scored on a 4‐point scale, from ‘0’ (no symptoms) to ‘3’ (terrible), with the total score ranging between ‘0’ and ‘30’.…”
Section: Methodsmentioning
confidence: 99%
“…18 The results of 10 questions were summed, and the total score is reported from 0-30.with higher scores signifying higher severity in LUTD .The questionnaire is found to be reliable to assess lower urinary tract symptoms in patients with chronic stroke as per the study concluded byMiyazato et.al in 2016. 12 Functional status was then evaluated using Barthel Index . It includes 10 fundamental items of ADL: feeding, grooming, bathing, dressing, bowel and bladder care, toilet use, ambulation, transfers, and stair climbing.…”
Section: Methodsmentioning
confidence: 99%
“…However the precise profile of lower urinary tract symptoms among patients with chronic stroke is still unclear according to a study by Miyazato M in 2017. 12 Previous studies have mostly focused on the prevalence of urinary incontinence (UI) while other symptoms such as urgency, daytime frequency and nocturia are rarely reported and quantified. 7 Assessment of severity and bother from symptoms is important, which leads to poor functional recovery and ultimately leading to poor functional status and medical help seeing behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Storage symptoms in stroke patients have been found to be significantly correlated with increasing age, male gender, high education, living alone, snoring, and co-existing medical conditions such as hypertension, and coronary heart disease ( 15 ). While, voiding symptoms, including slow stream and straining, are markedly associated with age and physical activity following stroke ( 98 ).…”
Section: Lower Urinary Tract Symptoms Are Prevalent In Aging and Majo...mentioning
confidence: 99%